Karl Popper's hypothetical deductive method in regular elementary school students in Peru. - González Andrade, Rodolfo (2023)
This essay aims to demonstrate that Karl Popper's falsificationist method favors the development of critical thinking in Regular Basic Education (RBE) students. One of its principles holds that absolute truth cannot be reached, since all knowledge has a temporary validity and that, by the logic of science, it can be improved with recent studies. Thus, the theory subject to refutation and corroboration is provisionally reformed until it is again reevaluated. This essay assumes that knowledge increases with the formulation of falsifiable hypotheses in the negative sense, and that hypotheses subject to skepticism, through questioning and criticism, stimulate student discussion. For the study of Popper's falsificationist method and its application in the teaching of Peruvian education, a specialized academic documentary base has been gathered to support the topic presented.